The effect of different first 200-m pacing strategies on blood lactate and biomechanical parameters of the 400-m sprint - Saraslanidis, P. J.; Panoutsakopoulos, V.; Tsalis, G. A.; Kyprianou, E. (European Journal of Applied Physiology, 2011)
The purpose of the present study was to evaluate the effect of three pacing strategies upon performance of the 400-m sprint. Eight healthy male physical education students participated in this study. Each participant performed a 200-m maximal test (200MAX) and three 400-m running tests in a random counterbalanced design. The 400-m tests were run with the first 200-m pace set at 98% (40098%), 95% (40095%), and 93% (40093%), respectively, of the effort for 200MAX. The stimulation of the lactate system was assessed by post-test blood lactate concentration (BLa). Running speed (RS) was controlled with time-keeping devices. Stride frequency (SF), stride length (SL) and lower extremity kinematics were acquired with video cameras operating at 100 fps at the 125 and 380-m marks of the tests. A two-way analysis of variance (ANOVA) with repeated measures was used to identify modifications caused by the pacing strategies used. Non-significant differences were revealed for BLa. The fastest 400-m race was run in 40093%, but performance was not significantly different (p > 0.05) among the examined pacing strategies. RS, SF and SL had significantly (p < 0.05) lower values in the 380-m mark when compared with the 125-m mark. In 40098%, both SF and SL decreased by approximately 13%, while SF and SL dropped 2.4 and 9.2%, respectively, in 40093%. In conclusion, lower peak BLa and less unfavorable modifications of running mechanics were recorded in 40093%, where time differential between the halves of the 400-m race was smaller, which eventually resulted in better performance.